Cross-cultural adaptation and validation of the European Heart Failure Self-care Behavior Scale for Brazilian Portuguese Adaptación transcultural y validación de la European Heart Failure Self-care Behavior Scale para el Portugués de Brasil Adaptação transcultural e validação da European Heart Failure Self-care Behavior Scale para o português do Brasil - Maria Karolina Feijó; Christiane Wahast Ávila; Emiliane Nogueira de Souza; Tiny Jaarsma; Eneida Rejane Rabelo (Revista Latino-Americana de Enfermagem, 2012)
OBJECTIVE: To adapt and validate a Brazilian Portuguese version of the European Heart Failure Self-Care Behavior Scale. METHODS: The cross-cultural adaptation (translation, synthesis, back-translation, expert committee review, and pretesting) and validation (assessment of face validity, content validity, and internal consistency reliability) were carried out in accordance with the literature. The European Heart Failure Self-Care Behavior Scale assesses key components of self-care: recognition of the signs and symptoms of decompensated heart failure (HF) and decision-making when these signs and symptoms arise. It comprises 12 items (range 12-60, where lower scores indicate better self-care). RESULTS: The sample comprised 124 HF patients with a mean age of 62.3 ± 12 years. The Cronbach's Alpha internal consistency was 0.70 and the intraclass correlation coefficient for reproducibility was 0.87. CONCLUSION: Face and content validity, internal consistency and reproducibility have lended validity and reliability for the use of the instrument in Brazil. OBJETIVO: Adaptar y validar European Heart Failure Self-Care Behavior Scale para uso en lengua portuguesa de Brasil. MÉTODOS: El proceso de adaptación cultural (traducción, síntesis, retro traducción, revisión por comité de expertos y pré test), validación (validez de facie, de contenido y confiabilidad) fue realizado según la literatura. La European Heart Failure Self-Care Behavior Scale evalúa los componentes-clave para el auto cuidado: reconocimiento de señales y síntomas de descompensación de insuficiencia cardiaca (IC) y la decisión cuando ocurren dichos síntomas. Se compone de 12 cuestiones (que van desde 12-60, en donde las puntuaciones bajas indican peor autocuidado). RESULTADOS: Fueron inclusos 124 pacientes con IC, con edad entre 62,3 ±12 años. La consistencia interna de las cuestiones presentó un Alfa de Cronbach de 0,70 y la reproducibilidad evaluada por el coeficiente de correlación. CONCLUSIÓN: La validad de fase, de contenido, la consistencia interna y la reproducibilidad concedieron validad y confiabilidad al instrumento para uso en Brasil. OBJETIVO: adaptar e validar a European Heart Failure Self-Care Behavior Scale para uso na língua portuguesa do Brasil. MÉTODOS: o processo de adaptação cultural (tradução, síntese, retrotradução, revisão por comitê de especialistas e pré-teste) e validação (validade de face, de conteúdo e fidedignidade) foi realizado de acordo com a literatura. A European Heart Failure Self-Care Behavior Scale avalia os componentes-chave para o autocuidado: reconhecimento dos sinais e sintomas de descompensação da insuficiência cardíaca (IC) e a tomada de decisão na ocorrência desses sintomas. É composta por 12 questões (variando de 12-60, baixos escores indicam melhor autocuidado). RESULTADOS: foram incluídos 124 pacientes com IC com idade de 62,3±12 anos. A consistência interna das questões apresentou um alfa de Cronbach de 0,70 e a reprodutibilidade avaliada pelo coeficiente de correlação intraclasse foi de 0,87. CONCLUSÃO: a validade de face, de conteúdo, a consistência interna e a reprodutibilidade conferiram validade e fidedignidade ao instrumento para uso no Brasil.